2016
DOI: 10.1016/j.hbrcj.2014.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of consistency properties of freshly mixed concrete by cone penetration test

Abstract: This study is directed to evaluate the ability of using cone penetration test as a simple method to investigate the consistency level of fresh concrete. A cone of 30°apex angle attached with different load values was used. Eighteen concrete mixes divided into three groups were conducted. Three types of coarse aggregate were tried. Crushed dolomite, round gravel, and crushed basalt all of 20 mm maximum grain size were investigated. For each type of coarse aggregate, six levels of concrete consistency calibrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…The observed low slumps also caused reduction of the flexural and split tensile strengths of the SFRC. The highest slump of 29 cm was obtained at 0.4 w/c ratio and 40% cement content and can be classified as very high according to the classification given by Abd Elaty and Ghazy (2016). Therefore, it can be concluded that careful selection of w/c ratio and cement content is very important to obtain SFRC with desirable mechanical properties.…”
Section: Resultsmentioning
confidence: 93%
“…The observed low slumps also caused reduction of the flexural and split tensile strengths of the SFRC. The highest slump of 29 cm was obtained at 0.4 w/c ratio and 40% cement content and can be classified as very high according to the classification given by Abd Elaty and Ghazy (2016). Therefore, it can be concluded that careful selection of w/c ratio and cement content is very important to obtain SFRC with desirable mechanical properties.…”
Section: Resultsmentioning
confidence: 93%
“…Consistency and index of viscosity of the fluid fraction of reconstituted rice pasta pudding, prepared from the dry‐crystallised mix, were determined using the back extrusion method. These properties were measured using a Texture Analyzer (TA.XT Plus; Stable Micro Systems, Surrey, UK) set to the following parameters: pre‐test speed of 1 mm/s, test speed of 1 mm/s, post‐test speed of 10.0 mm/s, distance of 30 mm and trigger force of 5 g (Abd‐Elaty and Ghazy 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Within this study, various tests were carried out to investigate the workability of polymer added cement grouts. The cone penetrometer (fall cone) test is one of the usable tests to investigate the workability of cement pastes [20][21][22]. The cone penetrometer test was performed to investigate the workability of fresh grout mixes.…”
Section: Workability Testsmentioning
confidence: 99%